In vivo imaging reveals unique neutrophil transendothelial migration patterns in inflamed intestines. Issue 6 (November 2018) - Sullivan, David; Bui, Triet; Muller, William; Butin-Israeli, Veronika; Sumagin, Ronen
Abstract Neutrophil (PMN) infiltration of the intestinal mucosa is a hallmark of gastrointestinal inflammation, with significant implications for host defense, injury and repair. However, phenotypic and mechanistic aspects of PMN recruitment in inflamed intestines have not been explored in vivo. Using novel epithelial/PMN fluorescence reporter mice, advanced intravital imaging and 3D reconstruction analysis, we mapped the microvasculature architecture across the intestinal layers and determined that in response toSalmonella /endotoxin-induced inflammation, PMN transendothelial migration (TEM) was restricted to submucosal vessels. PMN TEM was not observed in villus or crypt vessels, proximal to the epithelium that underlies the intestinal lumen, and was partially dependent on (C-X-C motif) ligands 1 (CXCL1) and 2 (CXCL2) expression, which was found to be elevated in the submucosa layer. Restricted PMN extravasation at the submucosa and subsequent PMN interstitial migration may serve as a novel regulatory step of PMN effector function and recruitment to the luminal space in inflamed intestines.